Censorship in South Asia : cultural regulation from sedition to seduction - Kaur, Raminder; Mazzarella, William, 1969- (Indiana University Press, 2009)
"Censorship in South Asia offers an expansive and comparative exploration of cultural regulation in contemporary and colonial South Asia. These provocative essays by leading scholars broaden our understanding of what censorship might mean -- beyond the simple restriction and silencing of public communication -- by considering censorship's productive potential and its intimate relation to its apparent opposite, 'publicity.' The contributors investigate a wide range of public cultural phenomena, from the cinema to advertising, from street politics to political communication, and from the adjudication of blasphemy to the management of obscenity"--Provided by publisher